Use It or Lose It: Environmental Enrichment as a Means to Promote Successful Cognitive Aging - Karyn M. Frick; Jamie D. Benoit (The Scientific World Journal)
Environmental enrichment has become increasingly utilized in rodent models of aging and neurodegenerative disease in order to prevent or reverse cognitive decline and neuronal dysfunction. However, the potential application of this body of work to human cognitive aging has rarely been discussed. The present article provides an overview of the rodent research that has tested the effects of environmental enrichment on hippocampal and neocortical function, and the types of memories mediated by these brain regions. Although data from models of neurodegenerative disease are presented, primary emphasis is given to studies of aging rodents and to methodological issues (e.g., age, treatment duration, treatment type) central to the mnemonic effectiveness of enrichment treatment. The implications of this work for human cognitive aging are discussed.